Cyber Democracy Versus Controlling Shareholders: The Implications of E-Voting System for Corporate Governance - Kuo-Pin Yang (International Journal of Informatics and Information Systems, 2019)
Based on the ideology of cyber democracy, Taiwan government has just begun to require the publicly-listed companies to implement the practice of e-voting system in stockholder meetings since 2012. One of the objectives of this mandate is to promote stockholder's activism to rectify the phenomenon of excess control associated with controlling shareholders, who dominate the boards of directors but own disproportionate ownership, to comply with the principle of one-share-one-vote. Though with good intention, the effectiveness of the e-voting system remains a question, given that it has been implemented only for a short period of time. In addition, the function of some auxiliary practices to supplement e-voting system such as director nomination also needs to be tested. This study proposes three hypotheses regarding the relationships among e-voting, board nomination, excess control, and firm performance. Using the data of 829 Taiwanese publicly-listed companies across the time period between 2012 and 2014, this study finds that the separate adoption of e-voting and board nomination increases the level of excess control and is, thus, detrimental to firm performance. On the other hand, the simultaneous adoption of the two practices can significantly decrease the level of excess control of controlling shareholders, which, in turn, contributes to firm performance. The findings bring important implications to corporate governance and policy formulation of the administration.